1994
DOI: 10.1021/j100073a035
|View full text |Cite
|
Sign up to set email alerts
|

Time Resolution of Electronic Transitions of Photosynthetic Reaction Centers in the Infrared

Abstract: Electronic transitions of the special pair excited state, P*, and of its positive ion, P+, have been identified by transient infrared spectroscopy in the 170&2000-~m-~ region. The P* transition is present immediately (ca. 300 fs) after light absorption and decays with time constant 3.4 ps. The P+ transition appears with time constant 3.4 ps. The transition dipoles of these transitions are both measured to have a squared projection of 0.63 onto the direction of the ground state to Qv-(870 nm) transition. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 7 publications
5
32
1
Order By: Relevance
“…Significant differences exist in both the amide I and cofactor regions of the spectra reported here and those of dry lipid films (37). These two preparations are known to differ functionally, with the most noticeable differences being the absence of a peak around 1640 cm-1, a much diminished feature around 1660 cm"-l", and the presence of a band around 1700 cm-' in the solution RC.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Significant differences exist in both the amide I and cofactor regions of the spectra reported here and those of dry lipid films (37). These two preparations are known to differ functionally, with the most noticeable differences being the absence of a peak around 1640 cm-1, a much diminished feature around 1660 cm"-l", and the presence of a band around 1700 cm-' in the solution RC.…”
Section: Discussionmentioning
confidence: 60%
“…The initial, small positive component of the kinetics in Fig. 3 implies that the band being probed is broader than =50 cm-, which may correspond to an electronic transition of P* at even lower frequency than the electronic transition reported previously (37). It now appears likely that a weak electronic absorption spectrum could underlie the vibrational spectrum over the whole region 1560-1960 cm-'.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Recently, rapid kinetics have been observed in anisotropy measurements applied to the P and B bands [10,21,31,39,51]. It is found that prior to ET, there exist a few steps in the P and B bands.…”
Section: ð1:1þmentioning
confidence: 99%
“…These bands have conventionally been assigned to the Q y electronic transitions of the P (870 nm), B (800 nm), and H (870 nm) components of RCs. By considering that the special pair P can be regarded as a dimer of two 2 s. h. lin et al ultrafast dynamics and spectroscopy 3 bacteriochlorophylls, the P band can be assigned to the lower excitonic band of P. By taking into account some difference in the protein environment in the L and M branches [2,3,[6][7][8][9][10][17][18][19][20][21]23,[30][31][32][33][34]41,42,46,47,52], the 800-nm band can be attributed to B L and B M [30][31][32][33][34][35][36][37][38][39][40][41][42]46,47]. The vibrational frequency of the special pair P and the bacteriochlorophyll monomer B have also been extracted from the analysis of the Raman profiles [39,40,42,44,51].…”
Section: Introductionmentioning
confidence: 99%